2020
DOI: 10.1186/s40364-020-00197-1
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms underlying CD19-positive ALL relapse after anti-CD19 CAR T cell therapy and associated strategies

Abstract: Chimeric antigen receptor (CAR) T cell therapy, especially anti-CD19 CAR T cell therapy, has shown remarkable anticancer activity in patients with relapsed/refractory acute lymphoblastic leukemia, demonstrating an inspiring complete remission rate. However, with extension of the follow-up period, the limitations of this therapy have gradually emerged. Patients are at a high risk of early relapse after achieving complete remission. Although there are many studies with a primary focus on the mechanisms underlyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 125 publications
0
56
1
Order By: Relevance
“…However, autologous BCMA CAR-T cells take at least 2-4 weeks to prepare and are mainly available in specialized medical centers, limiting its utility in individuals with rapid PD. For elderly patients (≥ 75 years old) and patients who have been heavily pretreated, it could be difficult to generate sufficient amount of autologous BCMA CAR-T cells [54,180]. The high incidence of CRS and NTX as well as grade ≥ 3 hematologic AEs associated with the pre-conditioning lymphodepletion are also major concerns, even though the BCMA CAR-T cells were effective for R/R MM patients [124].…”
Section: Bcma-targeted Therapeutics and Future Perspectivesmentioning
confidence: 99%
“…However, autologous BCMA CAR-T cells take at least 2-4 weeks to prepare and are mainly available in specialized medical centers, limiting its utility in individuals with rapid PD. For elderly patients (≥ 75 years old) and patients who have been heavily pretreated, it could be difficult to generate sufficient amount of autologous BCMA CAR-T cells [54,180]. The high incidence of CRS and NTX as well as grade ≥ 3 hematologic AEs associated with the pre-conditioning lymphodepletion are also major concerns, even though the BCMA CAR-T cells were effective for R/R MM patients [124].…”
Section: Bcma-targeted Therapeutics and Future Perspectivesmentioning
confidence: 99%
“…Yet the current results could not exclude the possibility that T cell-mediated immunity in host might have played a role in recognition of murine-based CD19 CAR. As an exogenous fusion protein, extracellular domain of CAR, especially murine-derived CARs, could possibly trigger T cell-based immunological rejection in which CD8+ T subpopulation particularly plays a pivotal role ( 5 , 17 , 18 ). Numerous clinical studies show that T cell response could be observed when murine-derived CAR-T was used to treat hematological malignances and solid tumors ( 19 , 20 ).…”
Section: Resultsmentioning
confidence: 99%
“…A study showed that CAR T-cells derived from young donors had greater expansion ability with more memory-like phenotypes but inferior cytotoxicity than those derived from geriatric donors ( 122 ). Moreover, c-Jun overexpression ( 123 ) and the immune-suppressive bone marrow microenvironment ( 124 ) are likely to be parameters related to antigen-positive relapse in CAR T-cell therapy.…”
Section: Challengesmentioning
confidence: 99%